Augmented expression of TSPO after intracerebral hemorrhage: a role in inflammation? - Frederick Bonsack; Cargill H. Alleyne; Sangeetha Sukumari‐Ramesh (2016)
Intracerebral hemorrhage (ICH) is a potentially fatal stroke subtype accounting for 10–15 % of all strokes. Despite neurosurgical intervention and supportive care, the 30-day mortality rate remains 30–50 % with ICH survivors frequently displaying neurological impairment and requiring long-term assisted care. Although accumulating evidence demonstrates the role of neuroinflammation in secondary brain injury and delayed fatality after ICH, the molecular regulators of neuroinflammation remain poorly defined after ICH. In the present study, ICH was induced in CD1 male mice by collagenase injection method and given the emerging role of TSPO (18-kDa translocator protein) in neuroinflammation, immunofluorescence staining of brain sections was performed to characterize the temporal expression pattern and cellular and subcellular localization of TSPO after ICH. Further, both genetic and pharmacological studies were employed to assess the functional role of TSPO in neuroinflammation. The expression of TSPO was found to be increased in the peri-hematomal brain region 1 to 7 days post-injury, peaking on day 3 to day 5 in comparison to sham. Further, the TSPO expression was mostly observed in microglia/macrophages, the inflammatory cells of the central nervous system, suggesting an unexplored role of TSPO in neuroinflammatory responses after ICH. Further, the subcellular localization studies revealed prominent perinuclear expression of TSPO after ICH. Moreover, both genetic and pharmacological studies revealed a regulatory role of TSPO in the release of pro-inflammatory cytokines in a macrophage cell line, RAW 264.7. Altogether, the data suggest that TSPO induction after ICH could be an intrinsic mechanism to prevent an exacerbated inflammatory response and raise the possibility of targeting TSPO for the attenuation of secondary brain injury after ICH.